2006
DOI: 10.1097/01.blo.0000205878.43211.44
|View full text |Cite
|
Sign up to set email alerts
|

Medial Fibula Transport with the Ilizarov Frame to Treat Massive Tibial Bone Loss

Abstract: Therapeutic Study, Level IV (case series). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 21 publications
0
32
2
2
Order By: Relevance
“…The reported time for hypertrophy of the fibula varies from one to two years or from two to four years; however, Tuli et al stated that no significant change in the diameter of the fibula is observed after five years (6,17). Fracture of tibialized fibula was not reported in most studies of fibular centralization with different techniques (3,5,6,(9)(10)(11). Keeting et al reported one stress fracture of the fibula in 16 cases of fibular transfer that were treated with sufficient immobilization time.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The reported time for hypertrophy of the fibula varies from one to two years or from two to four years; however, Tuli et al stated that no significant change in the diameter of the fibula is observed after five years (6,17). Fracture of tibialized fibula was not reported in most studies of fibular centralization with different techniques (3,5,6,(9)(10)(11). Keeting et al reported one stress fracture of the fibula in 16 cases of fibular transfer that were treated with sufficient immobilization time.…”
Section: Discussionmentioning
confidence: 95%
“…At 5-year follow up two of the seven patients walked wearing orthoses for protection of the leg from trauma. All of patients were adults (10). However, in another study of fibular transfer in two children because of fracture and infection with defects of 11 and 12 cm, the time for transfer and retaining Ilizarov device was 2.5 to 4 months with protection and an additional one to two months thereafter.…”
Section: Results Of Various Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Su tratamiento es complejo y controvertido, y entre las técnicas de reconstrucción se cuentan el transporte óseo, 2,5 los autoinjertos óseos libres o vascularizados, 3,6 las megaprótesis, 7,8 la técnica descrita por Masquelet con la "membrana inducida" 9,10 y los aloinjertos óseos molidos [11][12][13] o estructurales. 4,[14][15][16][17] La elección del tratamiento dependerá del sitio y el tamaño del defecto, el estado del miembro y sus partes blandas, la edad del paciente, la disponibilidad de injertos óseos de banco y, por supuesto, de la experiencia del cirujano.…”
Section: Discussionunclassified
“…9,10 Hay vasta experiencia en el uso de aloinjertos para el tratamiento de defectos segmentarios diafisarios en las resecciones tumorales, 16,19,20,24,27 no así en los defectos de origen traumático. [1][2][3][4]24 El uso de aloinjertos, sobre todo estructurales, se ha incrementado especialmente en las últimas décadas, hecho que se relaciona con el aumento de la cantidad y calidad de los bancos de huesos y tejidos, 24,29-32 los cuales procesan, conservan y atienden la bioseguridad de estos últimos, haciendo que los injertos sean cada vez de más fácil acceso para el cirujano ortopédico.…”
Section: Discussionunclassified